Soil greenhouse gas emissions from a sisal chronosequence in Kenya - Wachiye, Sheila; Merbold, Lutz; Vesala, Timo; Rinne, Janne; Leitner, Sonja; Räsänen, Matti; Vuorinne, Ilja; Heiskanen, Janne; Pellikka, Petri (Elsevier, 2021)
Sisal (Agave sisalana) is a climate-resilient crop grown on large-scale farms in semi-arid areas. However, no studies have investigated soil greenhouse gas (GHGs: CO2, N2O and CH4) fluxes from these plantations and how they relate to other land cover types. We examined GHG fluxes (Fs) in a sisal chronosequence at Teita Sisal Estate in southern Kenya. The effects of stand age on Fs were examined using static GHG chambers and gas chromatography for a period of one year in seven stands: young stands aged 1–3 years, mature stands aged 7–8 years, and old stands aged 13–14 years. Adjacent bushland served as a control site representing the surrounding land use type. Mean CO₂ fluxes were highest in the oldest stand (56 ± 3 mg C m-2 h-1) and lowest in the 8-year old stand (38 ± 3 mg C m-2 h-1), which we attribute to difference in root respiration between the stand. All stands had 13–28% higher CO₂ fluxes than bushland (32 ± 3 mg C m-2 h-1). CO2 fluxes in the wet season were about 70% higher than dry season across all sites. They were influenced by soil water content (WS) and vegetation phenology. Mean N2O fluxes were very low (<5 µg N m-2 h-1) in all sites due to low soil nitrogen (N) content. About 89% of CH4 fluxes were below the detection limit (LOD ± 0.02 mg C m-2 h-1). Our results imply that sisal plantations have higher soil CO2 emissions than the surrounding land use type, and the seasonal emissions were largely driven by WS and the vegetation status. Methane and nitrous oxide are of minor importance. Thus, soil GHG fluxes from sisal plantations are a minor contributor to agricultural GHG emissions in Kenya.